2014
DOI: 10.17221/7342-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of additive and dominance variance for litter size components in rabbits

Abstract: Additive, dominance, and permanent environmental variance components were estimated for the number of kits born alive, number of kits born dead, and total number of kits born of a synthetic rabbit line (called Pannon Ka). The data file consisted of 11 582 kindling records of 2620 does collected between the years 1996-2013. The total number of animals in the pedigree files was 4012. The examined traits were evaluated using single-trait and two-trait (number of kits born alive-dead) animal models containing all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
9
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 21 publications
4
9
2
Order By: Relevance
“…Contrary to us, in Nagy et al (2013Nagy et al ( , 2014, the narrow-sense heritability remained nearly unaltered irrespectively of whether dominance deviations were considered in the model or not, and narrow-sense heritability was similar or lower than dr 2 . In Nagy et al (2013Nagy et al ( , 2014, the consideration of dominance deviations improved the quality of the fit of the models. In our case, an improvement of the fit quality was never observed when adjusting dominance deviations: in the case of the A and V lines because the dominance deviations are negligible, and in the case of the H line because additive variation is nearly completely confounded with dominance variation.…”
Section: Genetic Trendscontrasting
confidence: 88%
See 1 more Smart Citation
“…Contrary to us, in Nagy et al (2013Nagy et al ( , 2014, the narrow-sense heritability remained nearly unaltered irrespectively of whether dominance deviations were considered in the model or not, and narrow-sense heritability was similar or lower than dr 2 . In Nagy et al (2013Nagy et al ( , 2014, the consideration of dominance deviations improved the quality of the fit of the models. In our case, an improvement of the fit quality was never observed when adjusting dominance deviations: in the case of the A and V lines because the dominance deviations are negligible, and in the case of the H line because additive variation is nearly completely confounded with dominance variation.…”
Section: Genetic Trendscontrasting
confidence: 88%
“…In other rabbit populations (Nagy et al, 2013(Nagy et al, , 2014, also ignoring inbreeding when computing D R and fitting YS as fixed effect, estimates of the ratio of dominance variance to the phenotypic variance (dr 2 ) were of similar magnitude to our estimates for the H line. Contrary to us, in Nagy et al (2013Nagy et al ( , 2014, the narrow-sense heritability remained nearly unaltered irrespectively of whether dominance deviations were considered in the model or not, and narrow-sense heritability was similar or lower than dr 2 . In Nagy et al (2013Nagy et al ( , 2014, the consideration of dominance deviations improved the quality of the fit of the models.…”
Section: Genetic Trendssupporting
confidence: 75%
“…Nevertheless, in this study it was only observed when dominance replaced other random effects. Apart from earlier studies (Nagy et al, 2013b;2014) where relatively small dominance effects (0.05-0.08) were reported for litter size traits there are Nagy et al (2014) for different litter size composite traits in Pannon White and in Pannon White Large rabbits using single trait models. However, Nagy et al (2014) also analyzed two trait models including dominance and, in that case, the observed breeding values stability substantially decreased (0.38-0.79).…”
Section: Resultsmentioning
confidence: 75%
“…The DNA was extracted from 31 (27 and 4 from maternal lineages 1-2) PK, 25 (1, 1, 4, 14, 4 and 1 from maternal lineages 1-6) PL and 22 (2, 1, 12 and 7 from maternal lineages) PW blood samples using commercially available NucleoSpin Blood Kit according to manufacturer's protocol (Macherey-Nagel GmbH & Co. KG, Germany). A 332-base pairs (bp) fragment of the mitochondrial D-loop region was amplified by polymerase chain reaction (PCR) using forward (5'-CACCATCAGCACCCAAAG-3') (Melo-Ferreira et al, 2009) and reverse primers (5'-ATTTAAGAGGAACGTGTGGG-3') (Pierpaoli et al, 1999). PCRs were performed in a 25 μL volume containing 0.2 μM of each primer and using Emerald AMP GT PCR Master Mix (Takara Bio Inc, Japan) according to the manufacturer's protocol.…”
Section: Molecular Analysismentioning
confidence: 99%